Multiple gastrointestinal haemangiomatosis: A report of two cases - Shina Adefarakan; Nyaweleni Tshifularo (Wolters Kluwer Medknow Publications, 2024)
Gastrointestinal (GI) haemangiomatosis is a very rare cause of GI bleeding in children. Due to this fact, making the diagnosis sometimes is delayed. In this case report, two different patients with multiple GI haemangiomatosis are presented. Of note is an 8 year old male with a previous history of a vascular malformation of the face presented with features of bowel obstruction (intussusception) and a history of recurrent blood in stool. At laparotomy, multiple haemangiomatosis were seen on the small bowel, right colon, liver, diaphragm and on the body of the gallbladder. Surgical management with excision of the enteric lesions and stapled anastomosis was done.